The political philosophy of Henry Sidgwick - Miller, D (Cambridge University Press, 2020)
Why has Sidgwick's political philosophy fallen into oblivion while his ethics continues to be celebrated? Not because his performance in that field was inferior, nor because his choice of topics has become outdated, nor because his conclusions were largely conservative. Instead the problem stems from the weight he attached to common sentiments and beliefs in his application of the utility principle, illustrated by his treatment of topics such as secession and colonialism. Moreover his Elements of Politics is arranged in such a way that he never has to confront the basic question of what makes states legitimate. This means that neither political moralists, who want to see the utility principle applied in more radical fashion, nor political realists, for whom the problem of establishing political order is central, find much to commend in his political philosophy.